Enhancing Children's Cognitive Skills through Play-Based Early Childhood Education at RA Nurul Iman Leuwimunding, Majalengka - Fajari, Alka (Sekolah Tinggi Agama Islam Kuningan (STAIKuningan), 2025)
Backround: Despite growing evidence supporting play-based learning for cognitive development, many early childhood education (ECE) institutions in Indonesia, particularly in semi-urban settings, still emphasize teacher-centered academic approaches. This creates tension between developmental appropriateness and academic pressure from parents and market expectations.Objective: This study aimed to explore the implementation of play-based learning and its effectiveness in enhancing cognitive skills of children aged 4–6 years at RA Nurul Iman Leuwimunding, Majalengka, and identify contextual barriers and enabling factors.Method: A qualitative case study approach was employed, involving 160 classroom observation sessions, 43 in-depth interviews with stakeholders (teachers, parents, head of institution, and children), two focus group discussions, and document analysis over six months. Data were analyzed using constant comparison and thematic analysis informed by grounded theory.Findings and Implications: Six major themes emerged: (1) significant tension between academic pressure and developmental appropriateness, with academic drills occupying 42% of learning time versus 8% for structured play; (2) substantial gap between teachers' conceptual understanding of play's value and technical competence to facilitate cognitive-focused play (100% recognize importance but only 17% can explain cognitive mechanisms); (3) successful adaptation of play-based approaches in resource-constrained settings; (4) critical role of teacher professional development; (5) low parental engagement in supportive play at home despite significant potential; and (6) absence of systematic monitoring of cognitive development through play. Targeted professional development, strategic parental engagement programs, curriculum integration frameworks, and systematic monitoring systems are essential to optimize play-based learning implementation.Conclusion: While play-based learning offers substantial potential for enhancing early cognitive development, its effectiveness depends critically on addressing knowledge gaps, institutional support, and stakeholder alignment in semi-urban ECE contexts.